2014
DOI: 10.1209/0295-5075/105/47009
|View full text |Cite
|
Sign up to set email alerts
|

Polariton condensation with saturable molecules dressed by vibrational modes

Abstract: Polaritons, mixed light-matter quasiparticles, undergo a transition to a condensed, macroscopically coherent state at low temperatures or high densities. Recent experiments show that coupling light to organic molecules inside a microcavity allows condensation at room temperature. The molecules act as saturable absorbers with transitions dressed by molecular vibrational modes. Motivated by this, we calculate the phase diagram and spectrum of a modified Tavis-Cummings model, describing vibrationally dressed two-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 57 publications
1
59
0
Order By: Relevance
“…In semiconductor microcavities, the necessary relaxation from the reservoir typically relies on exciton-polariton and polaritonpolariton scattering. In contrast, microscopic models for organic polariton lasing have suggested that vibronic coupling can play a more important role for dissipating excess momentum than exciton-polariton and polariton-polariton scattering [41][42][43]. In this picture, high-frequency intramolecular vibrational modes allow exciton-polaritons to scatter directly from the reservoir toward the lower energy levels [44].…”
Section: Resultsmentioning
confidence: 99%
“…In semiconductor microcavities, the necessary relaxation from the reservoir typically relies on exciton-polariton and polaritonpolariton scattering. In contrast, microscopic models for organic polariton lasing have suggested that vibronic coupling can play a more important role for dissipating excess momentum than exciton-polariton and polariton-polariton scattering [41][42][43]. In this picture, high-frequency intramolecular vibrational modes allow exciton-polaritons to scatter directly from the reservoir toward the lower energy levels [44].…”
Section: Resultsmentioning
confidence: 99%
“…(1) Direct dipole-dipole interactions at typical intermolecular distances in strong-coupling experiments only provide small corrections [31][32][33] and are thus neglected here for simplicity and generality. In the single-excitation subspace,Ĥ S is exactly solvable, with two types of eigenstates: (i) upper (UP) and lower (LP) polaritons…”
mentioning
confidence: 99%
“…That also implies the low-temperature which with weaker spin relaxation is beneficial to the formation of polarons, that can also be seen from the finite temperature pair propagator as presented in this paper. We present in Appendix.A a brief discussion of the variational approach in mean-field approximation which is valid in the weak interacting regime with non-too-low density [11], for the polaron dressed by the partially polarized excitations-cloud, however, the mean-fields approximation sometimes overestimates the interaction effect [12] in the strongly interacting regime (with tightly bound dimers) where the self-trapping, soliton, and breather are harder to formed than that in the weakly bound pairs (e.g., the BCS superfluid state in the non-Fermi-liquid picture). The stable repulsive polarons are most likely to be found in the side away from the Feshbach resonance (for gases) where polaron energy is large and positive (with 1/k F a ≫ 1; a ψφ is the scattering length related to the impurity-majority interaction, which is produced by the attractive potential and k F is the fermi wave vector), while in strong scattering region (1/k F a 1), the tightly-bound molecule (within Fermi-liquid picture) could also be found which with binding energy E b = 2 /2a 2 m > 0 [9,13], as experimentally realized in Ref.…”
Section: Introductionmentioning
confidence: 99%